Molecular cloning of a human small intestinal apolipoprotein B mRNA editing protein. - Hadjiagapiou, C (1994)
Mammalian small intestinal apolipoprotein B (apo B) mRNA undergoes posttranscriptional cytidine deamination with the production of an in frame stop codon and the translation of apo B48. We have isolated a cDNA from human jejunum which mediates in vitro editing of a synthetic apo B RNA template upon complementation with chicken intestinal S100 extracts. The cDNA specifies a 236 residue protein which is 69% identical to the apo B mRNA editing protein (REPR) cloned from rat small intestine [Teng, B., Burant, C. F. and Davidson, N. O. (1993) Science 260, 1816-1819] and which, by analogy, is referred to as HEPR. HEPR does not contain the carboxyl-terminus leucine zipper motif identified in REPR but contains consensus phosphorylation sites as well as the conserved histidine and both cysteine residues identified as a Zn2+ binding motif in other cytidine deaminases. The distribution of HEPR mRNA was predominantly confined to the adult small intestine with lower levels detectable by reverse-transcription polymerase chain reaction amplification in the stomach, colon and testis. These differences in the structure and distribution of the human as compared to the rat apo B mRNA editing protein suggest an important evolutionary adaptation in the mechanisms restricting apo B48 production to the small intestine.